Investment behavior and yields in some West German industries - Hugo Dicke; Peter Trapp (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
Net investment plays a crucial role for the economic development of a country. It contributes to the growth of real income and to the supply of jobs. Therefore, in view of sluggish growth and rising unemployment in Germany, the government as well as the Deutsche Bundesbank and the Council of Economic Experts have repeatedly pointed out the need to promote overall investment. Looking at the share of fixed investment in GDP in the German economy which is relatively high by international standards the complaints about the weakness of investment appear to be somewhat exaggerated. However, a closer look at the investment numbers published by the Deutsche Bundesbank (1983a, 1984) shows that the structure of domestic capital formation has changed dramatically since 1960. While investment by the non-financial business sector excluding housing accounted for 55 per cent of total investment in 1960, it has declined to some 30 per cent in the early 1980s (Figure 1) . Investment in residential construction and public investment have increased their share from about 44 per cent to more than two thirds in the early 1980s. Thus, instead of using more resources for enlarging and improving productive capacities, an increasing share of domestic savings has been channeled into projects the choice of which has not been made according to private profitability but from the point of view of social benefits. Among these projects are expenditures on infrastructure, public swimming pools, city halls, hospitals, family homes etc., which increase social consumption but hardly contribute to improve the competitiveness of the German industry in domestic and in international markets.
Keywords: 330